Treatment of VPI with Customized Pharyngeal Flaps: One Size Does Not Fit All. Issue 4 (14th April 2022) - Boudiab, Elizabeth M.; Peshel, Emanuela C.; Ibrahim, Yousef; Gupta, Rohun; Chaiyasate, Kongkrit; Shaheen, Kenneth; Rontal, Matthew; Thottam, Prasad; Antonio Ysunza, Pablo
Abstract : Background: Failure of complete closure of the velopharyngeal sphincter results in velopharyngeal insufficiency (VPI), which may severely interfere with speech. The pharyngeal flap remains a common procedure for correcting VPI. We aimed to study whether customization of pharyngeal flaps using a dynamic preprocedural assessment can result in successful outcomes in the surgical treatment of VPI, despite variations in surgical technique. Methods: This is a retrospective review of patients between the ages 4 and 18 years old with VPI who underwent surgical correction by one of four surgeons at our institution. All four surgeons used a superiorly based pharyngeal flap (SBPF) with slight variations in operative technique. All patients also received an evaluation by the speech and language pathologist that included nasometry, multiplanar videofluoroscopy, and flexible videonasopharyngoscopy. Individualized preoperative planning was performed based on the findings. Results: In total, 158 patients (92%) demonstrated overall successful correction of VPI, defined by a normal post-operative mean nasalance. Thirteen patients (8%) presented with resonance improvement but persistent abnormal mean nasalance. The most common causes of failed VPI correction were inferior migration and/or shrinking of the pharyngeal flap. There was a nonsignificant association between surgical technique and unsuccessful corrections. Conclusions: The optimal surgical approach for performing pharyngeal flaps to correct VPI is individualized, customizing the procedure based on preoperative imaging. This study demonstrates that despite variations in surgical techniques for performing SBPF, high rates of success can be achieved when adequate surgical planning is based on imaging findings.